The Process Quality Control Method Based on Coupling Machining Sensor Network. (22nd May 2014) - Zhao, Liping; Diao, Guangzhou; Yao, Yiyong
To monitor the dynamic changes of process quality and reduce the quality fluctuation in machining process, a process quality control method based on coupling machining sensor network (CMSN) is proposed to improve product quality. The advantage of CMSN is to combine the complex network with sensor technology. The purpose of this paper is to explore influence of coupling relationships between machining errors on the product quality by analyzing the stability of CMSN. Firstly, the mapping rules between machining process and network elements are provided to construct the topological model of CMSN. Next some performance indices of sensor nodes are defined and calculated to explore the self-organization stability of CMSN so that the appropriate sensor configuration can be selected to ensure the local stability of machining process. On this basis, the whole stability of CMSN is investigated by analyzing the nodes coupling so that the error accumulations are analyzed to improve product quality. Finally, a case study is provided to verify the feasibility of proposed method, in which Monte Carlo simulation is used to produce required quality data. The whole stability of CMSN for blade machining is discussed. It is expected that the proposed method can provide some guidance for machining process.